2019
DOI: 10.1029/2019wr024810
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Snow Albedo Estimates From MODIS and Their Impact on Snow Water Equivalent Reconstruction

Abstract: Snow albedo is a dominant control on snowmelt in many parts of the world. An empirical albedo decay equation, developed over 60 years ago, is still used in snowmelt models. Several empirical snow albedo models developed since show wide spread in results. Remotely sensed snow albedos have been used in a few studies, but validations are scarce because of the difficulty in making accurate in situ measurements. Reconstruction of snow water equivalent (SWE), where the snowpack is built in reverse, is especially sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 63 publications
2
77
0
Order By: Relevance
“…From recent work (Bair et al, 2018b), we have shown that the SNOWPACK (Lehning et al, 2002a, b;Bartelt and Lehning, 2002) model is capable of accurate SWE prediction when supplied only with snow depth for precipitation as well as the other requisite forcings (i.e., radiation, snow albedo, temperatures, and wind speed). Over a 5-year period using hourly in situ measured energy balance forcings and a snow pillow for validation at a high-elevation site in the western US, the SWE modeled by the numerical snow cover model SNOWPACK showed a bias of −17 mm, or 1 % (Bair et al, 2018b).…”
Section: Previous Work With Akah Snow Measurementsmentioning
confidence: 98%
See 3 more Smart Citations
“…From recent work (Bair et al, 2018b), we have shown that the SNOWPACK (Lehning et al, 2002a, b;Bartelt and Lehning, 2002) model is capable of accurate SWE prediction when supplied only with snow depth for precipitation as well as the other requisite forcings (i.e., radiation, snow albedo, temperatures, and wind speed). Over a 5-year period using hourly in situ measured energy balance forcings and a snow pillow for validation at a high-elevation site in the western US, the SWE modeled by the numerical snow cover model SNOWPACK showed a bias of −17 mm, or 1 % (Bair et al, 2018b).…”
Section: Previous Work With Akah Snow Measurementsmentioning
confidence: 98%
“…The authors report overestimation of the measured snow depth at the calibration station, even after questionable adjustments to the snow albedo and other model parameters. For example, the snow and ice albedo is given as 0.20 to 0.30 (Table 3, Shakoor and Ejaz, 2019), which would make it 0.10 to 0.20 lower than some of the lowest measured broadband albedo values for dirty snow (Bair et al, 2019b;Skiles and Painter, 2016). They attribute the overestimation to problems with the precipitation measurements, common for high-elevation stations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the Decadal Strategy identifies that key goals are improving measurements and modeling of albedo as a component of Earth's land surface, and understanding hazards in mountainous terrain [13]. Even with opportunities to improve satellite measurements of albedo in the future, Bair et al, [14] demonstrated that current remotely-sensed albedos are of value and provide better results than traditional age-decay model approaches.…”
Section: ∝=mentioning
confidence: 99%